Flipped Classroom at MBA -Effective Teaching Innovation Model for Strategic Management (Global Journal of Management and Business Research, 2018)
Purpose: Recent technological developments have given rise to blended learning classrooms. An inverted (or flipped) classroom is a specific type of blended learning design that uses technology to move lectures outside the classroom and uses learning activities to move practice with concepts inside the classroom. Methodology: This project introduces the idea of "flipped lecturing" to a group of second-year undergraduate students of MBA. The aim of flipped lecturing is to provide much of the "content delivery" of the lecture in advance, so that the lecture hour can be devoted to more in-depth discussion, problem solving, Students were provided with online lectures in advance of their lectures. Findings: Many of the characteristics of the flipped classroom teaching model, illustrated with some practical solutions offered to the subject Strategic Management. Pedagogical benefits of the model are highlighted along with potential challenges to its use. Results: The result indicated that implementing Flipped classroom have potential benefits for students while they engage themselves in learning with innovative teaching pedagogy as my results. Conclusion: The concept of student comfortability with learning activity is presented and can be developed high in light of learning environments research.
Keywords: flipped classroom; strategic management; social media; teaching innovation; MBA